2011
DOI: 10.1016/j.ydbio.2010.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 10 represses premature cell differentiation during establishment of the intestinal progenitor niche

Abstract: Spatio-temporal regulation of the balance between cell renewal and cell differentiation is of vital importance for embryonic development and adult homeostasis. Fibroblast growth factor signaling relayed from the mesenchyme to the epithelium is necessary for progenitor maintenance during organogenesis of most endoderm-derived organs, but it is still ambiguous whether the signal is exclusively mitogenic. Furthermore, the downstream mechanisms are largely unknown. In order to elucidate these questions we performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 63 publications
0
17
0
2
Order By: Relevance
“…Interestingly, studies in the embryonic lung have shown that Sox9 is not regulated by WNT/β-CATENIN; rather, it is likely downstream of FGF signaling (Chang et al., 2013, Rockich et al., 2013). Moreover, Fgf10 has been demonstrated to play a role in suppressing cytodifferentiation in the developing intestine (Nyeng et al., 2011). Thus, it is interesting to speculate that fibroblast growth factor signaling may play a role regulating progenitor cell proliferation during the pseudostratified stage.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, studies in the embryonic lung have shown that Sox9 is not regulated by WNT/β-CATENIN; rather, it is likely downstream of FGF signaling (Chang et al., 2013, Rockich et al., 2013). Moreover, Fgf10 has been demonstrated to play a role in suppressing cytodifferentiation in the developing intestine (Nyeng et al., 2011). Thus, it is interesting to speculate that fibroblast growth factor signaling may play a role regulating progenitor cell proliferation during the pseudostratified stage.…”
Section: Discussionmentioning
confidence: 99%
“…A distinct alternative model is that Fgf8 and Sox2 promote sensory competence by inducing a state of increased pluripotency. Both factors can promote formation of stem cells or multi-potent progenitors associated with early stages of tissue development (Graham et al, 2003; Nyeng et al, 2011; Tucker et al, 2010; reviewed by Lanner and Rossant, 2010). Thus, elevating Fgf8 or Sox2 could reverse early stages of differentiation of non-sensory cell types, thereby making cells more susceptible to Atoh1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of viable endoderm, the atretic precursor mesoderm involutes by a mechanism other than cell death. Recent work by Nyeng et al indicates that the loss of Fgf10 expression results in the premature differentiation of the progenitor niche in this region whereas over expression result in the expansion of this niche [12]. Together, these data suggest a more complex mechanism of duodenal atresia formation whereby a combination of endodermal cell death and terminal differentiation of progenitor cells results in formation of this defect.…”
Section: Discussionmentioning
confidence: 97%